In situ phase transformation synthesis of unique Janus Ag2O/Ag2CO3 heterojunction photocatalyst with improved photocatalytic properties - Jo, Wan-Kuen; Kumar, Santosh; Yadav, Poonam; Tonda, Surendar (Applied Surface Science, 2018)
Herein, Ag2O/Ag2CO3 nanocomposite with unique Janus morphology was synthesized by a facile ion-exchange followed by an in situ phase transformation method with precise control of its nucleation and growth processes. Contrary to conventional synthetic procedures of Janus architectures, the present Janus system was constructed without the need for surfactants or toxic chemicals. Most importantly, the visible-light-absorbing Janus Ag2O/Ag2CO3 nanocomposite exhibits a remarkable performance toward the degradation of Rhodamine B and 4-chlorophenol, far superior to that observed for bare Ag2CO3. The obvious enhancement of the photocatalytic performance of this nanocomposite is mainly attributed to the intimate Ag2O/Ag2CO3 interface created by its exceptional Janus architecture, which in turn allows for rapid charge transfer processes. Additionally, the Janus system exhibited a high photostability during recycling experiments with no significant change in the degradation activity. (C) 2018 Published by Elsevier B.V.